Surgical management of distal radius fractures using ligamentotaxis – A prospective study - Santosh S Deshpande; Aniket C Deshmukh; Rohit P Chauthe; Mayur C Veerkar; Shubham S Jadhav (Asian Journal of Medical Sciences, 2025)
Background: Distal radius fractures are among the most prevalent fractures, particularly in older adults. These fractures can lead to significant functional impairment if not managed appropriately. Various treatment modalities exist, but surgical interventions such as ligamentotaxis and external fixation have gained prominence in managing comminuted distal radius fractures. Aims and Objectives: The primary objective of this study was to evaluate the functional outcomes of surgical management of comminuted distal radius fractures using ligamentotaxis and external fixation. Materials and Methods: This prospective study included a cohort of 30 patients who underwent surgical management of comminuted distal radius fractures. The fractures were classified using the AO classification system, and ligamentotaxis was performed using external fixators over a 2-year period. Post-operative functional outcomes were assessed through clinical evaluations, range of motion measurements, and the Gartland and Werley score at regular intervals up to 6-month post-surgery. Results: The findings revealed that 84% of the patients achieved excellent to good functional outcomes, while 16% experienced fair to poor results. The suboptimal outcomes were primarily attributed to complications such as residual pain and stiffness. In addition, a marginal of cases exhibited complications including malunion, restricted wrist movement, and finger stiffness. Conclusion: This prospective study demonstrates that ligamentotaxis using external fixation is an effective method for managing comminuted distal radius fractures, with most patients achieving excellent to good functional outcomes.